Antimicrobial peptides and their therapeutic potential as anti-infective drugs: A review - Muhammad, Azhen Fatih (Sulaimani Journal for Pure and Applied Sciences, 2019)
Antimicrobial peptides (AMPs), also referred to as host defense peptides, are small molecular weight proteins with broad spectrum antimicrobial activity against bacteria viruses, fungi, and parasites. The AMPs areimportant components of innate immune systems. They are believed to be existed more than 2.6 billion years ago as part of the innate immunity in primitive organisms. The antimicrobial activity of these natural peptidesmakes them possible candidates in the development of new drugs against the multidrug resistant bacterial strains that have emerged recently. However, development of new therapeutics from the natural source Anti-infective drugs (AMPs) seems to be faced with many problems, such as toxicity, rapid, degradation and inability to maintain required concentrations in the target tissues. This review focuses on the therapeutic possibility of thenatural antimicrobial peptides, the advantages and disadvantages of these compounds when used for topical and systemic applications, as well as their possible utilization in the development of new anti- infective drugs.
Keywords: Antimicrobial peptides; AMPs; Antiinfective